Generic and specific fitness profile of elite youth greco-roman wrestlers; Differences according to quality and weight category - Skugor, K.; Stajer, V.; Zugaj, N., Gilic, B.; Karnincic, H. (SportMont, 2023)
This study aimed to investigate the validity of the Specific Wrestling Fitness Test (SWFT), correlating it with generic anaerobic tests in elite youth wrestlers and determining whether wrestlers differ according to quality and weight categories in all tests. The research included 23 advanced-level Greco-Roman wrestlers (aged 16-19 years) who were divided into two quality categories (National team members and Non-team members) and two weight categories (lighter and heavier). Variables included anthropometric characteristics, generic fitness tests, and SWFT. Results evidenced that only vertical jump height was associated with SWFT (Pearson`s R=0.48, p<0.05). Team members had higher results in the vertical jump height (p=0.02, moderate ES), while wrestlers from the heavier category had higher body mass (p=0.001, large ES) and body height (p=0.01, large ES) than lighter wrestlers. Moreover, wrestlers did not differ in the SWFT according to quality and weight categories. SWFT was not associated with generic fitness tests, possibly because of its high specificity. Furthermore, team members and non-team members did not differ in the SWFT, which could be explained by the fact that only advanced-level wrestlers were included in this study. Thus, future studies should include lower-quality wrestlers and different testing protocols.